Approaches and strategies in next generation science learning - Khine, Myint Swe; Saleh, I. (IGI Global, 2013)
Approaches and Strategies in Next Generation Science Learning examines the challenges involved in the development of modern curriculum models, teaching strategies, and assessments in science education in order to prepare future students in the 21st century economies. This comprehensive collection of research brings together science educators, researchers and administrators interested in enhancing the teaching and learning of next generation science.